1996
DOI: 10.1002/(sici)1097-4644(199608)62:2<275::aid-jcb15>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

hnRNP proteins and B23 are the major proteins of the internal nuclear matrix of HeLa S3 cells

Abstract: The nuclear matrix is the structure that persists after removal of chromatin and loosely bound components from the nucleus. It consists of a peripheral lamina-pore complex and an intricate internal fibrogranular structure. Little is known about the molecular structure of this proteinaceous internal network. Our aim is to identify the major proteins of the internal nuclear matrix of HeLa 53 cells. To this end, a cell fraction containing the internal fibrogranular structure was compared with one from which this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 93 publications
4
70
0
2
Order By: Relevance
“…Such a key role of hnRNP-U in BER of oxidative DNA damage, probably in association with transcription, was quite unexpected. These results, together with the fact that hnRNP-U, also identified independently as scaffold attachment factor A, is a major component of the nuclear matrix (47), suggest a critical dynamic role of the nuclear architecture in the repair of oxidized bases during transcription (48).…”
Section: Discussionmentioning
confidence: 86%
“…Such a key role of hnRNP-U in BER of oxidative DNA damage, probably in association with transcription, was quite unexpected. These results, together with the fact that hnRNP-U, also identified independently as scaffold attachment factor A, is a major component of the nuclear matrix (47), suggest a critical dynamic role of the nuclear architecture in the repair of oxidized bases during transcription (48).…”
Section: Discussionmentioning
confidence: 86%
“…Nucleophosmin copurifies with the nuclear matrix (25), and it seems reasonable to suggest that it is the interaction between this protein and CTCF that leads to the appearance of CTCF in the matrix fraction. Chromatin immunoprecipitation experiments have shown that nucleophosmin and CTCF colocalize at insulator sites in vivo, presumably explaining our observation that the HS4 insulator sequence is also concentrated in the matrix fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Standard PCR of matrix DNA was carried out in 25-l reactions [2.5 l of 10X buffer͞0.5 l of 10 mM dNTP mix͞0.5 l each of 10 M forward and reverse primer͞0. 25 PCRs were carried out with 6C2 cell genomic DNA. Primer sequences are available on request.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a proteolytic product of the C proteins, unwinding protein 2 (UP2), influences the activity of DNA polymerase ␣, suggesting that hnRNPs C1 and C2 may also influence some aspects of DNA metabolism (29)(30)(31). Many of the hnRNP proteins, including hnRNPs C1 and C2, associate with the nuclear matrix (18,42,43). Interestingly, telomeres and the DNA replication machinery are also associated with this nuclear structure (14), and DNA polymerases ␣/primase are required for telomerase activity (15).…”
Section: Discussionmentioning
confidence: 99%